A double-blind, randomised, placebo-controlled study of roxithromycin and doxycycline combination, roxithromycin alone, or matching placebo for 12 weeks in adults with frequent exacerbations of chronic obstructive pulmonary disease. Issue 1 (December 2015) - Shafuddin, Eskandarain; Mills, Graham; Holmes, Mark; Poole, Phillippa; Mullins, Peter; Black, Peter
Abstract Background Azithromycin prophylaxis has been shown to reduce COPD exacerbations but there is poor evidence for other antibiotics. We compared exacerbation rates in COPD patients with a history of frequent exacerbations (at least three moderate or severe COPD exacerbations in the past two years) during a 12-week treatment course and over a subsequent 48-week follow up period. Results 292 patients were randomised to one of three treatments for 12 weeks: roxithromycin 300 mg daily and doxycycline 100 mg daily (n = 101); roxithromycin 300 mg daily (n = 97); or matching placebos (n = 94). There were no differences in the annualised moderate and severe exacerbation rates after treatment with roxithromycin/doxycycline (2.83 (95 % CI 2.37-3.40)) or roxithromycin only (2.69 (2.26-3.21)) compared to placebo (2.5 (2.08-3.03)) (p = 0.352 and p = 0.5832 respectively). Furthermore, there were no differences in the annualised exacerbation rates during 12-week treatment with roxithromycin/doxycycline (1.64 (95 % CI 1.17-2.30)), roxithromycin only (1.75 (1.24-2.41)) or placebo (2.23 (1.68-3.03)) (p = 0.1709 and p = 0.2545 respectively). There were also no significant differences between groups for spirometry or quality of life scores over either the 12-week treatment or 48-week post-treatment periods. Both active treatments were associated with nausea but otherwise adverse events were comparable among treatment groups. Conclusions Twelve-weeks of prophylaxis with roxithromycin/doxycycline combination or roxithromycin alone did not reduce COPD exacerbations in patients with history of frequent exacerbations. These findings do not support the use of these antibiotics to prevent exacerbations in COPD patients. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTRN12615000052538 ). Date of first registration: 22 January 2015.